Part-time work, underemployment and gender. Worker versus job explanations - Randi Kjeldstad; Erik H. Nymoen (Statistics Norway, Research Department, 2009)
The article analyses part-time work, both so-called voluntary and involuntary, in a gender perspective and discusses under what conditions women and men work part-time. The discussion is based on logistic regression models, including human capital, life-course- and household characteristics and job characteristics as independent variables. We use Norwegian Labour Force Survey data. The analysis shows that part-time work is a strongly gendered phenomenon, not only because it occurs much more frequently among women than among men, but also because the causes of part-time differ between the sexes. We find, as expected, that involuntary part-time is mainly tied to job characteristics, whereas voluntary part time is equally predicted by worker characteristics and job characteristics. The effect of gender is strong and significant, however less significant when controlling for job characteristics than when controlling for worker characteristics.
Keywords: J22; J23; J24; 330; Voluntary part-time; involuntary part-time; gender; job- and labour-market approach; individual- and life-course approach; time bargaining